2007
DOI: 10.1093/rpd/ncm175
|View full text |Cite
|
Sign up to set email alerts
|

Local diagnostic reference levels for some common diagnostic X-ray examinations in Tehran county of Iran

Abstract: Various researchers who have carried out national and international surveys have reported wide variations in patient dose arising from specific X-ray examinations. This study was carried out as a part of a comprehensive project to establish national diagnostic reference level (NDRL), for the first time, in Iran. Seven most common X-ray examinations in 11 projections were included. Thermo luminescence dosimeters (TLD-100) were used to measure entrance surface doses (ESDs). The study group consisted of 535 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
0
16
1
Order By: Relevance
“…for good radiographic image in this province 7 , 10 , 11 , 15 , 16 , 17 , 18 , 19 , 20 . As 4, 5 show, this weakness was also seen in Bahreyni Toosi et al in Tehran, Mashhad, and Sabzovar 15 , 16 , 20 …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…for good radiographic image in this province 7 , 10 , 11 , 15 , 16 , 17 , 18 , 19 , 20 . As 4, 5 show, this weakness was also seen in Bahreyni Toosi et al in Tehran, Mashhad, and Sabzovar 15 , 16 , 20 …”
Section: Discussionmentioning
confidence: 75%
“…India, and Bahreyni Toossi and Asadinezhad (20) in Tehran was used to obtain comparable data. Table 6 shows DRLs for different types of radiographic examinations in Sistan‐Baluchestan province and recent NRPB reports.…”
Section: Resultsmentioning
confidence: 99%
“…The patient exposure parameters of several radiographic projections recorded at KKUH were compared with their corresponding values at international hospitals (Iran, UK and Malaysia) ( Table 4). As can be seen from Table 4, the mean values of potential, current and ESD determined in this study were compared with the corresponding values reported in Iran (Toosi and Asadinezhad, 2007), the United Kingdom (Hart et al, 2002) and Malaysia (NG et al, 1998). The results in Table 4 indicated that the range of applied tube potential for all the projections at KKUH was higher than the corresponding range reported in the surveys Abdelhalim et al 9819 undertaken in Iran, United Kingdom and Malaysia.…”
Section: Resultsmentioning
confidence: 94%
“…The very wide variations in patient dose arising from a specific type of x-ray examination in different national and international hospitals suggest that significant reductions in the patient dose would be possible without affecting image quality. Various researchers who previously carried out national and international surveys also reported wide variations in patient dose arising from specific x-ray examination (Seeram et al, 2006;Toosi and Asadinezhad, 2007;Asadinezhad and Toosi, 2008). They suggested that the possible causes for varying patient dose levels could be the examination technique, clinical condition, skill of the radiologist, tube current, tube potential and focus to film distance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation